Recombinant Human Elastase Alters the Compliance of Atherosclerotic Tibial Arteries After Ex Vivo Angioplasty - Burke, Steven K; Bingham, Karen; Moss, Emma; Gottlieb, Daniel P; Wong, Marco D; Bland, Kimberly S; Franano, F Nicholas (Journal of cardiovascular pharmacology, 2016)
This study was designed to determine whether vonapanitase (formerly PRT-201), a recombinant human elastase, treatment can fragment the protein elastin in elastic fibers and cause dilation of atherosclerotic human peripheral arteries subjected to ex vivo balloon angioplasty. Seven patients undergoing lower limb amputation for peripheral artery disease or who died and donated their bodies to science donated 11 tibial arteries (5 anterior, 6 posterior) for this study. All arteries were atherosclerotic by visual inspection. The arteries underwent ex vivo balloon angioplasty and thereafter were cut into rings and studied on wire myographs where the rings were stretched and tension was recorded. After treatment with vonapanitase 2 mg/mL or vehicle control, myography was repeated and the rings were then subject to elastin content measurement using a desmosine radioimmunoassay and elastic fiber visualization by histology. The wire myography data were used to derive compliance, stress-strain, and incremental elastic modulus curves. Vonapanitase treatment reduced elastin (desmosine) content by 60% and decreased elastic fiber histologic staining. Vonapanitase-treated rings experienced less tension at any level of stretch and as a result had shifts in the compliance and stress-strain curves relative to vehicle-treated rings. Vonapanitase treatment did not alter the incremental elastic modulus curve. Vonapanitase treatment of atherosclerotic human peripheral arteries after ex vivo balloon angioplasty fragmented elastin in elastic fibers, decreased tension in the rings at any level of stretch, and altered the compliance and stress-strain curves in a manner predicting arterial dilation in vivo. Based on this result, local treatment of balloon angioplasty sites may increase blood vessel diameter and thereby improve the success of balloon angioplasty in peripheral artery disease.